Novel metabolite madeirone and neomarinone extracted from Streptomyces aculeoletus as marine antibiofilm and antifouling agents - Wissner, Julian L.; Almeida, Joana R.; Grilo, Inês R.; Oliveira, Jhenifer F.; Brízida, Carolina; Escobedo-Hinojosa, Wendy; Pissaridou, Panayiota; Vasquez, Marlen I.; Cunha, Isabel; Sobral, Rita G.; Vasconcelos, Vítor; Gaudêncio, Susana P. (Frontiers in Chemistry, 2024)
Introduction: Biofouling poses a significant economic threat to various marine industries, leading to financial losses that can reach billions of euros annually. This study highlights the urgent need for effective alternatives to traditional antifouling agents, particularly following the global ban on organotin compounds. Material and methods:Streptomyces aculeolatus PTM-346 was isolated from sediment samples on the shores of the Madeira Archipelago, Portugal. The crude extract was fractionated using silica flash chromatography and preparative HPLC, resulting in two isolated marinone compounds: madeirone (1), a novel marinone derivative discovered in this study, and neomarinone (2). The antifouling activities of these compounds were tested against five marine bacterial species and the larvae of the mussel Mytilus galloprovincialis. Additionally, in silico and in vivo environmental toxicity evaluations of madeirone (1) and neomarinone (2) were conducted. Results: Madeirone (1) demonstrated significant antibiofilm efficacy, inhibiting Phaeobacter inhibens by up to 66%, Marinobacter hydrocarbonoclasticus by up to 60%, and Cobetia marina by up to 40%. Neomarinone (2) also exhibited substantial antibiofilm activity, with inhibition rates of up to 41% against P. inhibens, 40% against Pseudo-oceanicola batsensis, 56% against M. hydrocarbonoclasticus, 46% against C. marina, and 40% against Micrococcus luteus. The growth inhibition activity at the same concentrations of these compounds remained below 20% for the respective bacteria, highlighting their effectiveness as potent antibiofilm agents without significantly affecting bacterial viability. Additionally, both compounds showed potent effects against the settlement of Mytilus galloprovincialis larvae, with EC50 values of 1.76 µg/mL and 0.12 µg/mL for compounds (1) and (2), respectively, without impairing the viability of the targeted macrofouling species. In silico toxicity predictions and in vivo toxicity assays both support their potential for further development as antifouling agents. Conclusion: The newly discovered metabolite madeirone (1) and neomarinone (2) effectively inhibit both micro- and macrofouling. This distinct capability sets them apart from existing commercial antifouling agents and positions them as promising candidates for biofouling prevention. Consequently, these compounds represent a viable and environmentally friendly alternative for incorporation into paints, primers, varnishes, and sealants, offering significant advantages over traditional copper-based compounds.